Sequence analysis of 18SrDNA gene from sagoplast degrading fungi - Tri Gunaedi; Arsyam Mawardi (The East Java Biological Society, 2021)
The bioplastic can be made from sago flour and known as sagoplast. It was widely known that for making bioplastic, the addition of acetic acid and glycerol are needed. Products that are air-dried are easy to grow fungi within a few weeks. This makes the basis for researchers to undestand more about the character and identity of the sagoplast degrading fungi. Characterization and identification were carried out by observed morphology and analyzing the 18SrDNA gene sequence of fungal isolates that had grown on the sagoplast. Fungal isolates morphology showed yellowish-orange color with white thread-like mycelia and a blackish brown mace with white thread-shaped mycelia. These characters of fungal morphology that similar with Aspergillus. The gene sequences of the fungal isolates were aligned with reference gene sequences of the fungi obtained from the Gen Bank of the National Center for Biotechnology Information (NCBI). Sequence data analysis was performed by using the Clustal X program to determine the kinship and taxonomy of the fungal isolates that able to degrade sagoplast. The result showed that two fungal isolates, DFSP.J1 and DFSP.J4, were found and demonstrated their ability for degrading sagoplast. Isolate DFSP.J1 is related to Aspergillus flavus strain PSU2 LC127086.1, while isolate DFSP.J4 is related to Aspergillus niger IFO4033 D63697.1.